Medusas zooplanctónicas (Cnidaria: Medusozoa) en la Bahía de Acapulco, Guerrero - Chávez Valero, Kevin Axel (Universidad Autónoma Metropolitana, 2025)
Planktonic jellyfish are invertebrates characterized by radial symmetry, primarily found in coastal and oceanic zones. Variations significantly influence their abundance and diversity in environmental conditions such as temperature and salinity. In this study, the spatial and temporal variations in the abundance, diversity, and distribution of zooplanktonic jellyfish in Acapulco Bay, Guerrero, were examined. Surface trawls were conducted using a standard conical zooplankton net with a 30 cm mouth diameter, one meter in length, and a mesh size of 250 μm. These trawls lasted for 10 minutes and were performed during the following periods: February 2017, February 2018, March 2020, November 2022, and March 2023 at four stations: Naval, Caleta (inner zone), Sinfonia, and Oceánica (outer zone). A total of 2,478 planktonic jellyfish were identified, belonging to forty-seven species in the Class Hydrozoa and one species in the Class Scyphozoa. The study results emphasized the influence of temperature on the seasonal diversity and abundance of jellyfish in Acapulco Bay. The salinity did not exhibit significant spatial or temporal variations in jellyfish abundance. Higher jellyfish abundance was recorded in the inner part of the bay (Naval), while the lowest abundance occurred in the oceanic zone (Oceánica). However, no significant variations in jellyfish abundance were observed across the five sampling periods. The most abundant jellyfish species included Obelia spp., Aglaura hemistoma, and Stauridiosarsia ophiogaster. Additionally, different associations with temperature were noted, leading to the grouping of planktonic jellyfish into distinct temperature intervals. The study also introduced eight new records of jellyfish in Acapulco Bay: Bougainvillia fulva, Corymorpha forbesii, Eucheilota paradoxica, Lizzia ferrari, Lovenella clausa, Rhopalonema funerarium, Sphaerocoryne bedoti, and Solmaris flavescens. Last, the research included redescribing Lizzia alvarinoae and reclassifying Eucheilota maasi from extinct to extant status. The results demonstrated the influence of temperature on the diversity and abundance of jellyfish in Acapulco Bay.; Las medusas planctónicas son invertebrados de simetría radial que se distribuyen principalmente en zonas costeras y oceánicas. No obstante, su abundancia y diversidad están influenciadas por las variaciones de las condiciones ambientales como la temperatura y la salinidad. En el presente estudio se analizó las variaciones espacio-temporales de la abundancia, diversidad y distribución de medusas zooplanctónicas en la Bahía de Acapulco, Guerrero. Se realizaron arrastres superficiales con una red estándar tipo cónica para zooplancton, de 30 cm de diámetro de boca, un metro de largo y con una luz de malla de 250 μm durante 10 minutos en los periodos de febrero de 2017, febrero 2018, marzo 2020, noviembre 2022 y marzo 2023 en las estaciones Naval, Caleta (zona interna), Sinfonía y Oceánica (zona externa). Se obtuvieron 2,478 medusas planctónicas identificadas en 47 especies de la Clase Hydrozoa y una de la Clase Scyphozoa. Los resultados del estudio destacaron la influencia de la temperatura en la diversidad y abundancia estacional de medusas en la Bahía de Acapulco. La salinidad no mostró variaciones espaciales ni temporales significativas en la abundancia de medusas. Se observó una mayor abundancia de medusas en la parte interna de la bahía (Naval), mientras que la menor abundancia se registró en la zona oceánica (Oceánica), sin embargo, no se identificaron variaciones significativas en la abundancia de medusas entre los cinco períodos de muestreo. Las especies de medusas con mayor abundancia fueron Obelia spp., Aglaura hemistoma y Stauridiosarsia ophiogaster. Adicionalmente se observaron diferentes asociaciones con la temperatura, a diferentes intervalos. El estudio también presentó ocho nuevos registros de medusas en la Bahía de Acapulco: Bougainvillia fulva, Corymorpha forbesii, Eucheilota paradoxica, Lizzia ferrari, Lovenella clausa, Rhopalonema funerarium, Sphaerocoryne bedoti y Solmaris flavescens. Por último, se realizó la re-descripción de Lizzia alvarinoae y el cambio de Eucheilota maasi de categoría de extinta a vigente. Los resultados demostraron la influencia de la temperatura en la diversidad y abundancia de las medusas de Bahía de Acapulco.